2019
DOI: 10.1177/0031512519860286
|View full text |Cite
|
Sign up to set email alerts
|

Combining 3D-MOT With Sport Decision-Making for Perceptual-Cognitive Training in Virtual Reality

Abstract: This study introduces a virtual life-sized perceptual-cognitive training paradigm that combines three-dimensional multiple object tracking (3D-MOT) with motor (Experiment 1) or perceptual (Experiment 2) sport decision-making tasks. We sought to assess the impact of training on task performance and determine optimal training conditions for improvement and learning. Fifty-seven participants were randomly assigned to one of four training conditions (isolated 3D-MOT, 3D-MOT combined with a decision-making task, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Concerning the chronic effects, training with dual-tasks improved both motor and cognitive performance. Bherer et al [51] suggested that dual-tasks training leads to the development of new perceptual strategies (optimizing attentional focus for the relevant clues in the task) that contribute to improved decision-making [52], as supported by some findings of the present review [21,26]. The significant increase in the duration of the quiet eye [45] after training with dual-tasks indicate that the athletes directed their attention to specific spots for a longer time to extract relevant information for the tactical decision.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Concerning the chronic effects, training with dual-tasks improved both motor and cognitive performance. Bherer et al [51] suggested that dual-tasks training leads to the development of new perceptual strategies (optimizing attentional focus for the relevant clues in the task) that contribute to improved decision-making [52], as supported by some findings of the present review [21,26]. The significant increase in the duration of the quiet eye [45] after training with dual-tasks indicate that the athletes directed their attention to specific spots for a longer time to extract relevant information for the tactical decision.…”
Section: Discussionsupporting
confidence: 65%
“…Secondly, the absence of a peer-review process would allow the inclusion of low methodological quality studies. Concerning the period of the review, we decided to include only recent articles (last six years, from January 2015 to May 2020) to reduce the methodological heterogeneity of the selected studies, since many of the current ones use tests and procedures recently proposed and validated (for example, 3D-motion [ 21 , 25 , 26 ]). Additionally, reviews on this topic were found in 2014, which would lead us to replicate the findings of previous reviews [ 15 , 16 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Table 3 in the Appendix), which seems to explain the lack of meaningful furthertransfer. Moreover, this lack also appears to be based on the specificity of the training task which includes some aspects of dynamic soccer situations but does not cover the perception and action combinations of these situations (Romeas, Chaumillon, Labbé, & Faubert, 2019). Thus, it could be argued that this dearth of several broad perception and action combinations may be one of the reasons for the absence of any further-transfer which is in line with a current review (Hadlow et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
“…In terms of future practical application, it is highly interesting if those further progression steps yield larger further-or even far-transfer effects. A first dual-task study indicates the general superiority of dual-compared to single tasktraining with the NT 3D-MOT (Romeas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For different team sports there exists previous work investigating the feasibility of VR for assessing the decision-making process of team sports athletes [ 19 , 23 , 48 ]. In a study conducted by Wirth et al they used 360° video footage displayed via an HMD to investigate PCS of soccer players [ 19 ].…”
Section: Background and Related Workmentioning
confidence: 99%